Stakeholders’ Engagement of Domestic MICE Tourism during a Crisis: A Case Study of the COVID-19 Pandemic - Kemthong, Janrapee (Journal of Business, Innovation and Sustainability (JBIS), 2023)
Consequences of the COVID-19 pandemic that affected to tourism industry included MICE became the considered sign for academic to study more specific research for strengthening business and people who involved in MICE industry. Besides, there are a little attention is given to stakeholders’ engagement of MICE tourism in Thailand particularly when they need to handle with a crisis. Therefore, this research objective is to study a stakeholders’ engagement of domestic MICE tourism during a crisis of the COVID-19. A qualitative approach was conducted by using semi-structured interview with 12 stakeholders of domestic MICE in two MICE cities in the North: Chiang Mai and Phitsanulok. A template analysis was employed to explore the research findings. The key points of this study are about stakeholders engagement process; 1) scene-setting to enhance awareness during the COVID-19 crisis naturally and rapidly occurred that highly affected stakeholders to make decision and online communication was applied completely, 2) the governmental stakeholders played significant role to facilitate online communication for updating information and providing training courses, and 3) making the change real with sustainable new MICE business processes included MICE product diversification became a crucial business strategy and IT knowledge, skill and experience became a critical resources for domestic MICE.